Treatment Delays in Primarily Resected Oropharyngeal Squamous Cell Carcinoma: National Benchmarks and Survival Associations. (31st July 2018) - Morse, Elliot; Judson, Benjamin; Husain, Zain; Burtness, Barbara; Yarbrough, Wendell G.; Sasaki, Clarence; Cheraghlou, Shayan; Mehra, Saral
Abstract : Objective: To characterize treatment delays in surgically treated oropharyngeal cancer, identify factors associated with delays, and associate delays with survival. Study Design: Retrospective cross‐sectional analysis. Setting: Commission on Cancer–accredited institutions. Subjects and Methods: We identified patients in the National Cancer Database with surgically treated oropharyngeal cancer. We characterized the durations of diagnosis‐to‐treatment initiation, surgery‐to‐radiation treatment, radiation treatment duration, total treatment package, and diagnosis‐to‐treatment end intervals as medians. We associated delays with patient, tumor, and treatment factors via multivariable logistic regression analysis and with overall survival by Cox proportional hazards regression. Results: In total, 3708 patients met inclusion criteria. Median durations of diagnosis‐to‐treatment initiation, surgery‐to‐radiation treatment, radiation treatment duration, total treatment package, and diagnosis‐to‐treatment end intervals were 27, 42, 47, 90, and 106 days, respectively. Medicaid and human papillomavirus (HPV) negativity were associated with delays. Delayed total treatment package and diagnosis‐to‐treatment end intervals were associated with decreased survival (hazard ratio [HR] = 1.81 [1.29‐2.54], P =. 001 and HR = 1.97 [1.39‐2.78], P <. 001, respectively); this was maintained following HPV stratification. Delays in the surgery‐to‐radiation treatment interval were associated with decreased overall survival in HPV‐negative but not HPV‐positive patients (HR = 2.05 [1.19‐3.52], P =. 010 and HR = 1.15 [0.74‐1.80], P =. 535, respectively). Diagnosis‐to‐treatment initiation and radiation treatment duration were not associated with overall survival in the overall cohort (HR = 1.21 [0.86‐1.72], P =. 280 and HR = 1.40 [0.99‐1.99], P =. 061, respectively); however, following stratification, delayed radiation treatment duration approached significance in HPV‐negative but not HPV‐positive patients (HR = 1.60 [0.96‐2.68], P =. 072 and HR = 1.35 [0.84‐2.18], P =. 220). Conclusion: Treatment durations identified here can serve as national benchmarks and for institutions to compare quality to their peers. Distinct benchmarks should be applied to HPV‐negative and HPV‐positive patients.